Difference and similarity in perception between green supply chain management in food industry and green supply chain management in generally in croatian companies - Opetuk, Tihomir; Kolar, Davor; Cajner, Hrvoje; Dukic, Goran (Zeszyty Naukowe. Organizacja i Zarządzanie, 2017)
Nowadays, the increase in greenhouse gas (GHG) emissions in the atmosphere is currently one of the most serious environmental treats. Due to GHG emissions we will be witnesses of climate change which will cause damaging impacts in the next few decades [1]. These will primarily affect the natural and human systems [2]. At the same time these emissions are also a limiting factor for the economic growth of some countries, especially those in the transition process [3]. One of the reasons for that is the protocol, adopted in 2012 at Doha 2012 UN Climate Change Conference COP18 CMP8, at which the industrial world agreed to reduce the emissions of greenhouse gases approximately 18% below 1990 levels by 2013-2020 [4]. In the meantime, also due to the climate change and the increase in environmental awareness all over the world, the concept of Green Supply Chain Management appeared. It is often defined as integrating environmental thinking into supply chain management [5].Within that concept many greening elements aimed at the reduction of materials, energy, waste, pollution and emissions, or promoting the usage of recyclable materials and renewable energy sources, are introduced in various segments of supply chains. The proof lies in number of examples from industry, as well as in significant interest of academic community that could be seen through research papers, doctoral thesis and research projects.